Situation Report: Poland, 30 April 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Letter of the 34 Was a "Domestic Affair", Professors Claim Jaroszewicz on Comecon Polish-East German Protocol on Trade Exchange Polish-Finish Trade Relations Trade Agreement with Uganda Polish-Austrian Trade Talks